The Impacts of the Training Programme and Education Achievement on Job Opportunities A Big Data Analytics - Ting, Tin Tin; Moh, Jing Wen; Aisshwarya Singaram; Peggy Soh; Pung, Jarn Yong; Lee, Kuok Tiung (Roman Science Publications, 2023)
Job opportunities are important for humans to earn economic value to sustain daily life. However, some people are unemployed, and some are unhappy with their current job. Job opportunities raise concern and attention from young people to ensure that they can have financial freedom and a lifestyle with a work-life balance. These studies examined the relationship between job opportunities with training programmes and education achievement using the large ICPSR dataset (>90,000 sample sizes). The relationship between the independent variables and the dependent variables are analysed, along with the mediating variables, which include the CGPA and rate of pay. Three data sets are merged, cleaned and transformed using IBM SPSS 23.0 and PROCESS Macro. The results showed the pattern that the training programme and education achievements positively impact job opportunities. The results of the mediation analysis show that the CGPA only mediates the positive relationship between educational achievement and job opportunities. Furthermore, the rate of pay as a mediator also is positively related to training programmes and job opportunities. This study is important in increasing the initiative of the people involved in the training programme and in achieving a higher level of education to secure better employment opportunities.